Health Care Workers Communication on Diabetes Mellitus Management in Hospital and Community Health Center - Sholihatul Maghfirah; Rohmadi Rohmadi (KEMAS: Jurnal Kesehatan Masyarakat)
Diabetes Mellitus (DM) patients require DM management for life. Research proved that good quality self-care behavior of DM patients in dr. Harjono Regional Public Hospital Ponorogo and in North Ponorogo Community Health Center were still low (28,6% in dr. Harjono Regional Public Hospital Ponorogo and 50% in North Ponorogo Community Health Center). Health care worker communication is related to self-care behavior of DM patients. Differences in hospital and community health center self-care behavior in the previous study results triggered a question on the differences in hospital and community health center workers communication. This study was conducted in 2017 and aimed to explain the difference of health care workers communication regarding DM management in hospital and community health center. This study used comparative research design with 32 respondents from dr. Harjono Regional Public Hospital Ponorogo and 31 respondents from North Ponorogo Community Health Center. The results showed that 78.1% of respondents in hospitals and 93.5% of respondents in community health center stated good health care workers communication. The Fisher’s Exact test found p value of 0.148 which meant that there was no difference in communication of healthcare workers in hospital and community health center. Most patients in both places suffered from DM for 1-5 years and required the same health care workers communication, therefore there was no difference in the communication of health workers in both places.